2021
DOI: 10.1007/s00253-021-11303-0
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of nitrogen cycling genes at a Midwest long-term ecological research site with different management practices

Abstract: Nitrogen fertilizer results in the release of nitrous oxide (N 2 O), a concern because N 2 O is an ozone-depleting substance and a greenhouse gas. Although the reduction of N 2 O to nitrogen gas can control emissions, the factors impacting the enzymes involved have not been fully explored. The current study investigated the abundance and diversity of genes involved in nitrogen cycling (primarily denitrification) under four agricultural management practices (no tillage [NT], conventional tillage [CT], reduced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…16 Similarly, Zheng and Cupples concluded that the relative abundance of certain nitrogen-cycle genes were affected by agricultural practices. 17 Therefore, there must be a careful balance between agricultural practices, soil nitrogen content, and the microbial community, and further studies regarding these interactions could uncover the variables and mechanisms.…”
Section: Biotechnologymentioning
confidence: 99%
See 1 more Smart Citation
“…16 Similarly, Zheng and Cupples concluded that the relative abundance of certain nitrogen-cycle genes were affected by agricultural practices. 17 Therefore, there must be a careful balance between agricultural practices, soil nitrogen content, and the microbial community, and further studies regarding these interactions could uncover the variables and mechanisms.…”
Section: Biotechnologymentioning
confidence: 99%
“…Behnke et al showed that crop rotation and cover crop use, which are common conservation practices that introduce nitrogen to the soil, alter the nitrogen cycle directly or indirectly thus impacting nitrous oxide generation 16 . Similarly, Zheng and Cupples concluded that the relative abundance of certain nitrogen‐cycle genes were affected by agricultural practices 17 . Therefore, there must be a careful balance between agricultural practices, soil nitrogen content, and the microbial community, and further studies regarding these interactions could uncover the variables and mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Chisel tillage increased all microbial N cycle genes (nifH, nirK, nirS, and nosZ) compared to no-till (Table 2). In a study from the Kellogg Biological Station in Michigan, each denitrification gene was also reduced in the no-till treatment compared to conventional tillage (Li and Cupples, 2021). Chisel tillage is used to help break down residues, which stimulates microbial activity through aeration and warmer soil conditions (Balesdent et al, 2000;Martens, 2000;Hu et al, 2021).…”
Section: Bacterial Denitrification Via Nirk Linked To Nitrous Oxide E...mentioning
confidence: 99%
“…Without fertilization, the leguminous cover crop, hairy vetch, contained similar N cycle gene expression as the fertilized no cover treatment (Hu et al, 2021). In a Michigan, USA study, Li and Cupples (2021) observed different tillage treatments within a corn-soybean-wheat rotation and found that no-till decreased copy numbers for each denitrification gene (nirK, nirS, and nosZ) compared to conventional tillage.…”
Section: Introductionmentioning
confidence: 96%